PENGARUH KEGIATAN LUKIS TIUP TERHADAP PERKEMBANGAN KREATIVITAS KARYA SENI ANAK USIA DINI KELOMPOK B DI TK KANTIL : THE INFLUENCE OF BLOW PAINTING ACTIVITIES ON THE DEVELOPMENT OF CREATIVITY OF ART WORKS OF EARLY AGE CHILDREN IN GROUP B IN KANTIL KINDERGARTEN - Intan Nia Indriani; Juli Yanti Harahap (incrementapedia, 2023)
The formulation of the problem in this study is whether there is an influence of blow painting activities on the development of creativity in group B early childhood art at Kantil Kindergarten T.A 2022/2023. The purpose of this study was to determine the effect of blow painting activities on the development of artistic creativity in group B early childhood at Kantil Kindergarten T.A 2022/2023. This study used a quantitative method (experimental) with a pre-experimental design, namely one group pretest-posttest design. The population in this study amounted to 22 children who were early childhood aged 4-5 years in group A and early childhood aged 5-6 in group B. The sample in this study were children aged 5-6 years in group B, totaling 15 children. . Data collection techniques using observation sheets. Data analysis techniques use statistical tests, namely data normality tests and hypothesis testing using the t-test. Based on the results obtained, it can be concluded that there is a significant influence of blow painting activities on the creativity of early childhood artwork. This is based on the results of the t-test, obtained Tcount = 4.212 and Ttable = 1.761. Therefore it can be concluded that Tcount>Ttable (4.212>1.761) which means Ho is rejected and Ha is accepted